3DPC literature review on the effects of mixture composition on constructability - Dillinger, Zachary T. (Kansas State University, 2024)
The advent of 3D printing technology offers an alternative building method to the construction industry by offering innovative solutions for complex and sustainable building designs. This research paper explores the critical aspects of 3D printed concrete mixture design and its applicability in constructing robust and efficient structures. The study reviews concrete mixtures explicitly tailored for 3D-printing, considering both fresh and hardened properties, and printability. Breaking down the individual mixture components and their effects on the concrete properties is critical to developing a proper mixture design. The influence of various parameters, such as binder composition, water ratios, aggregate size/quantity, chemical admixtures, and fiber reinforcement, on the mechanical properties, durability, and workability of 3D-printed concrete is investigated. Case studies testing the effects of concrete mixture components on the fundamental rheological (flow) properties needed to achieve printability and the mechanical properties needed for structural design are given. Additionally, examples of housing, infrastructure, and specialized architectural elements using 3D-printed concrete is presented.
Keywords: Concrete; 3DPC; Concrete mixture design; Rheology; 3D Printing